Comparative Genetic Analysis Of Wild Finger Millet Accessions Using Finger Millet And Maize Microsatellite Markers (Applied Biological Research, 2017)
The genomic information available for finger millet is very scarce though the  plant is a rich source of highly digestible proteins and dietary fibre with good  amounts of soluble and insoluble fractions. In present study, 64 maize and  finger millet genomic SSRs were used for cross transferability, identification  of polymorphic markers and genetic diversity of finger millet, both cultivated  and wild species. Out of 64 SSRs, only 43 (67%) were amplified across the  finger millet genotypes. The PIC values of all the polymorphic loci across the  23 finger millet genotypes varied from 0.04 to 0.47 (average value 0.17).  Based on the parameters of PIC values ≥ 0.26, gene diversity ≥0.43,  inbreeding coefficient ≥ 0.60, the SSR loci UGEP33, UMC1858, UMC1805,  and UMC2163 were found highly polymorphic. Comparison of SSR  polymorphism in finger millet genotypes revealed that microsatellites of  maize were more polymorphic and were able to identify more diversity in  finger millet genotypes than the finger millet SSRs. Good correlations were  found between genetic diversity analysis in differentiation of finger millet  genotypes using finger millet and maize microsatellite markers. Dendrogram  generated through UPGMA analysis grouped all the 23 genotypes clustered  them into two major groups A and B with maximum similarity found  between genotype pairs T552, T622 and T507, T74. The genotype pairs T671  and T760; T187 and T 631, T824 showed lowest similarity in finger millet  which could be selected for hybrid plant production. The present study  enriched the finger millet genomics by identifying suitable polymorphic  markers of maize and finger millet, which can be used for diversity analysis,  cultivar identification and QTL mapping studies.
Keywords: Finger millet; SSR markers; genetic analysis; maize microsatellites